EFFECT OF BIOFERTILIZER,VERMICOMPOST AND PHOSPHATE FERTILIZER ON GROWTH AND YIELD OF CAULIFLOWER( Brassica oleraceae Var.botrytis) - Noor A. J.K. Al-Silmawy,; H. A. Abdul- Ratha, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field experiment was carried out at Agricultural Researchs and the Experiments Station in Wasit province during 2019-2020 season. This study was aimed to investigate the effect of three factors, the first being biofertilizer at three levels (without addition , a combination of Bacillus megaterium + Glomus mosseae and complet combination of G. mosseae, Azotobacter chroococcum, B. megaterium and Azospirillum brasilense). the second factor was three levels of vermicompost (without,3,6 Mg ha-1).The third factor included three levels of triple superphosphate (0, 40 and 80%) of the fertilizer recommendation. The treatment were distributed in a factorial experiment according to a randomized complete block design. Results showed that the bilateral interaction between the biofertilizer added in an integrated form and vermicompost at the level of 6 Mg ha-1 had a significant effect on all studied properties, while the triple interaction between the biofertilization treatments added as an integrated combination with 6 Mg h-1 of vermicompost and 80% of the mineral fertilizer recommendation   showed the highest averages for the studied traits (flower disc weight, disc weight with leaves, pink disc diameter, total yield, nitrogen and phosphorous content of fruits), which reached 2.524 kg, 4.353 kg, 35.10 cm, 75.71 Mg ha-1, 4.237%, 0.727% respectively in comparison  to the control treatment that gave the lowest averages in all the above traits, which amounted to (1.081 kg, 1.624 kg, 25.10 cm, 32.43 Mg ha-1, 1.893%, 0.210% ) on the sequence.